GERMINATION OF SEEDS AND INITIAL DEVELOPMENT OF Celosia cristata L. SEEDLINGS IN DIFFERENT SUBSTRATES - FERREIRA, Elane Grazielle Borba de Sousa; MATOS, Valderez Pontes; SENA, Lúcia Helena de Moura; SALES, Anna Gorett de Figueiredo Almeida (Scientia Agraria, 2008)
The present work had as objective to evaluate the substrate effect different in the germination and initial development of plantulas of Celosia cristata L. seedlings. The seeds had souving on and into blotting paper, vermiculite, coconut fiber and sand at 25 ºC, under continuous light. The following parameters were analyzed: germination (%), first germination count (%); index germination speed and length (cm) of the primary root. The experiment was a completely randomized design with four replications of 25 seeds. The best results for germination (%) and germination speed were oblained into and on blotting paper. However, the substrate on coconut fiber and vermiculite had promoted the biggest development of the seedlings primary roots but they didn’t favour the germination.